(untitled) (Journal of Architectural Design, 2023)
Muqarnas (Arab. mqrns ) is a type of architectural decoration; a complex shape resulting from the superposition of arched cups (cells). In architecture, it is widely used to make the upper part of mihrab, takhman, shelf, etc., with a 4/6/8 corner base, into a dome, semi-dome, the space between the wall and the ceiling of buildings, column heads, etc. At first, it had a simple shape, later it became more complex and was used for decorative purposes. Muqarnas varies in complexity depending on where it is used. The ends of the arches with a curved surface are brought forward, forming a support for the upper row. On the surface, these whorls often form an equilateral triangle, with 2 or more whorls intersecting at different angles to form calyxes